Pan-Slavism and Slavophilia in Contemporary Central and Eastern Europe
XXVII, 428 p. 19 illus., 17 illus. in color.
Keywords: This collection is an important contribution in both the historical and contemporary analysis of Pan-Slavism. It places this concept in context of Yugoslavism, as well as Russian appeals to Slavic and Orthodox solidarity and competing European identity. This book will become a standard study on the topic through its comprehensive and systematic approach, covering most Slavic countries and not treating Pan-Slavism as just a type of failed meta nationalism, but as an important idea informing the Slavic world today. - Florian Bieber, Professor of Southeast European History and Politics, University of Graz, Austria The heyday of Pan-Slavism may be long gone, but the idea of the brotherhood of Slavs continues to inspire a range of cultural, civilisational and geopolitical imaginations in Europe. This book is a veritable treasure trove for anyone interested in the curious evolution of thisunderstudied phenomenon and its contemporary ramifications. - Filip Ejdus, Associate Professor, Faculty of Political Science, University of Belgrade, Serbia This book explores origins, manifestations, and functions of Pan-Slavism in contemporary Central and Eastern Europe, arguing that despite the extinction of Pan-Slavism as an articulated Romantic-era geopolitical ideology, a number of related discourses, metaphors, and emotions have spilled over into the mainstream debates and popular imagination. Using the term Slavophilia to capture the range of representations, the volume analyses how geopolitical discourses shape the identity and policies of a community, providing a comparative analysis that covers a range of Slavic countries in order to understand how Pan-Slavism works and resonates across geographic and political contexts. Mikhail Suslov is Assistant Professor in the Department of Cross-Cultural and Regional Studies at the University of Copenhagen, Denmark. Marek Čejka is Associate Professor in the Department of Territorial Studies at Mendel University in Brno, Czech Republic. Đorđević Vladimir is Assistant Professor in the Department of Territorial Studies at Mendel University in Brno, Czech Republic. .